Model Pembelajaran Direct Intruction Bermedia Video Pembelajaran untuk Meningkatkan Keterampilan Vokasional - R. Agtiani Putri; Murtadlo Murtadlo; Wagino Wagino (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Vocational skills as learning to provide provisions that are in accordance with students' abilities. The purpose of this study is to test the influence of the direct instruction model to improve students' vocational skills in SLB-C AKW IISurabaya. This study uses a quantitative approach using a pre-experimental design with a one group pretest-posttest design. The data collection technique uses tests. The results in this study showed that the average pretest score of 37.00 increased and the posttest result was 70.00. The results of data analysis show Zh 2.80 and Zt 1.96, then the interpretation is Ha > Ho. So, Ha is accepted, which means that it is evident that there is an influence of the Direct instruction learning model mediated by learning videos to improve vocational.